Retrospective analysis of the effect of acid-suppressant therapy on clinicopathologic parameters of cats with chronic kidney disease. Issue 6 (June 2018) - Gould, Emily; Klos, Jacob; Price, Josh; Harris, Tonya; Vaden, Shelly; Tolbert, M Katherine
Objectives: The aim was to retrospectively evaluate the effects of acid-suppressant therapy in a population of cats with chronic kidney disease (CKD). The study objectives were to evaluate the effects of acid-suppressant therapy on clinicopathologic variables and progression of CKD over time. Methods: The databases of two institutions were searched over an 11 year time span for cats fitting inclusion criteria for CKD. A total of 89 cats met the criteria for inclusion and were grouped according to either early (ie, stages 1–2) or advanced (ie, stages 3–4) CKD. Variables were statistically analyzed before and after treatment with either: (1) proton pump inhibitors (PPIs; n = 17), (2) histamine-2 receptor antagonists (H2RAs; n = 30), (3) combined acid-suppressant therapy (PPI + H2RA; n = 6) or (4) no acid-suppressant therapy (n = 36). Shapiro–Wilk testing and Q-Q plots were used to assess normality and variance, respectively. A complete randomized design with a mixed-effects repeated measures ANOVA was used to evaluate for differences in stage, treatment and time, as well as the interaction between these effects. Results: A significant increase in blood creatinine concentration was found over time independent of severity of CKD and treatment group ( P = 0.0087). A significant increase in blood sodium concentration (change of 3.12 mmol/l) was found independent of stage in cats receiving PPI therapy ( P = 0.0109). A significant decrease in total blood magnesium (change of 0.15 mmol/l) was detected in two cats with early CKD receiving combined acid suppressants ( P = 0.0025). Conclusions and relevance: Results of this retrospective study suggest that cats with CKD receiving PPI therapy may develop alterations in blood sodium concentrations but do not experience more rapid progression of CKD.